Design, development and experimental validation of a lightweight dual-arm aerial manipulator with a COG balancing mechanism. (April 2022) - Imanberdiyev, Nursultan; Sood, Sumil; Kircali, Dogan; Kayacan, Erdal
Abstract: In this work, we present the design, fabrication, and experimental validation of a lightweight, low inertia dual-arm manipulator with a center of gravity (COG) balancing mechanism, specifically designed for aerial manipulation missions. The developed system, consisting of the dual-arm base and two arms with 6 degrees of freedom (DOFs) each, weighs 2.5 kg in total with a maximum payload of 1.0 kg per arm. The dual-arm system is designed such that it can be attached to different multirotors without making major design modifications. In addition, the design of the arms is conceived to decrease the inertia of the arms by utilizing a timing belt-based transmission mechanism. Moreover, the proposed dual-arm design employs prismatic joints to introduce the following distinctive features: 1) ability of each arm to dynamically adjust its COG for better flight performance; 2) fully independent control of each arm for performing different tasks simultaneously; 3) extended workspace and reach of the arms for enhancing operational capability and improving safety during aerial manipulation missions. Since the proposed design has low inertia and a compensation mechanism to deal with the disturbances caused by the COG change, the developed dual-arm system can be mounted on multirotors equipped with standard autopilots, opening the door for the widespread use of dual-arm manipulators with the commercially available UAV platforms. To ensure the robustness of the mechanical structure, an analysis using finite element methods (FEM) is conducted. Extensive experimental flight tests are performed to evaluate the proposed dual-arm design with a hexarotor equipped with a common off-the-shelf autopilot. The experimental results show that the influence of the arms motion over the hexarotor stability is minor in contactless flight due to the low weight and inertia of the proposed dual-arm design. Furthermore, better hovering performance is achieved by exploiting the ability of the proposed design to compensate the dual-arm COG displacement.